Negotiating autonomy and authority in Muslim contexts - Bernards, Monique; Buitelaar, Marjo (Groningen studies in cultural change, 2013)
The present volume contains the proceedings of a workshop that took place as part of a larger project carried out by the Groningen Research School for the Study of the Humanities (GRSSH). The framework of the overall research perpsective was a study of the autonomy of culture and its components. In November 2006, colleagues from various departments at the University of Groningen who work in the field of islamic studies jointly organised a workshop on the subject of autonomy and Islam. For and from each of our disciplines, i.e. anthropology, psychology, pedagogy, philology and religious studies, internationally renowned scholars were invited to participate.